Capital Expenditure, Sales Growth, and Corporate Profitability: Panel Data Evidence from Indonesian Manufacturing Companies for the Period 2021–2024 - Sutari Sri rejeki; Dwi Astutik; Sabtarini Kusumaningsih; Titik Rianawati; Arini Novandalina (CV. Aksara Global Akademia, 2026)
This paper studies the effect of capital expenditure (CAPEX) and sales growth on Indonesian manufacturing firms profitability, controlling for firm size and debt to equity ratio (DER). Profitability is defined by Return on Assets (ROA). The analysis uses financial data from Bloomberg for an initial frame of 345 listed manufacturing firms over the period 2021–2024. After winsorising the continuous variables at the 1st and 99th percentiles and deleting incomplete firm-years, the working sample is an unbalanced panel of 1,223 firm-year observations from 332 firms. Static panel estimators were evaluated, and the Hausman test (χ²(4) = 34.40, p < 0.001) and the redundant fixed-effects test (F(331, 887) = 5.99, p < 0.001) supported a fixed-effects specification, estimated with standard errors clustered by firm. The results indicate that CAPEX has a statistically significant association with ROA (β = −16.55, p = 0.020). Given that CAPEX is recorded as a negative cash-outflow ratio, it means that higher investment intensity is related to higher profitability. Sales growth has a positive and substantial effect on ROA (β = 1.33, p < 0.001) and DER has a negative and significant effect (β = −0.015, p < 0.001), while firm size is not significant within firms. The findings are consistent with the resource-based view and pecking-order thinking and give practical implications for capital-budgeting and financing decisions in the post-pandemic recovery.